KONDISI RUMAH SEHAT DESA GAYAMAN KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Kartiningrum, Eka Diah (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2013)
House is a very important shelter basically for every people. but it contains of important meaning as a place to build a healthy and prosperous family life. The data of housing in Indonesia showed that 75.1% of the houses belonging to the Indonesian population are not healthy. Therefore, the aim of this study was to determine healthy housing in the Desa Gayaman Mojoanyar Mojokerto regency. Design of this study was descriptive, the variable is healthy house. Population in this study were 12 921 houses, and 30 samples were selected using quota sampling technique. This study had been conducted in Desa Gayaman Kec. Mojoanyar Kab. Mojokerto on June 5 to 10 June 2013 using check list sheets. The data were processed with editing, coding, scoring, tabulation and presented in frequency distribution tables Based on the results of the study showed that most of the respondents had an unhealthy houses as many as 30 respondents (100%). The components in unhealthy house, sanitation and residents can cause family status. So the healthy house should facilitate residents activities in order to dismiss unhealthy factors. The conclusions in this study is the majority of respondents in Desa Gayaman Kec. Mojoanyar Kab. Mojokerto have an unhealthy house. Therefore health workers should provide information to the public owning healthy house category, but they are expected to in the community to seek information about healthy livingmore activity and healthy house empowerment.Keywords: Family, Healthy Housing